2007
DOI: 10.1007/s00216-006-1036-7
|View full text |Cite
|
Sign up to set email alerts
|

Polar herbicides, pharmaceutical products, perfluorooctanesulfonate (PFOS), perfluorooctanoate (PFOA), and nonylphenol and its carboxylates and ethoxylates in surface and tap waters around Lake Maggiore in Northern Italy

Abstract: A survey of contamination of surface and drinking waters around Lake Maggiore in Northern Italy with polar anthropogenic environmental pollutants has been conducted. The target analytes were polar herbicides, pharmaceuticals (including antibiotics), steroid estrogens, perfluorooctanesulfonate (PFOS), perfluoroalkyl carboxylates (including perfluorooctanoate PFOA), nonylphenol and its carboxylates and ethoxylates (NPEO surfactants), and triclosan, a bactericide used in personal-care products. Analysis of water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
2
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(119 citation statements)
references
References 27 publications
12
93
2
12
Order By: Relevance
“…The PFHxA concentrations were also undetectable or low in all surface water samples (< 1.0-3.7 ng/l). The surface water concentrations reported here are on the low end of those reported in other coastal and fresh waters (Kallenborn et al 2004, Yamashita et al 2005, Tanaka et al 2006, Skutlarek et al 2006, deVoogt et al 2006, Weremiuk et al 2006, Loos et al 2007.…”
Section: Water Samplescontrasting
confidence: 45%
See 1 more Smart Citation
“…The PFHxA concentrations were also undetectable or low in all surface water samples (< 1.0-3.7 ng/l). The surface water concentrations reported here are on the low end of those reported in other coastal and fresh waters (Kallenborn et al 2004, Yamashita et al 2005, Tanaka et al 2006, Skutlarek et al 2006, deVoogt et al 2006, Weremiuk et al 2006, Loos et al 2007.…”
Section: Water Samplescontrasting
confidence: 45%
“…PFCs are suspected to be carcinogenic and may also act as endocrine disruptors (White et al 2011). In an effort to better understand the environmental and organismal impacts of such compounds, many studies have assessed contamination in water supplies (Post et al 2009), wastewater treatment plants Guo 2010), and a wide variety of environmental samples including fresh and marine waters (Kallenborn et al 2004, Yamashita et al 2005, Tanaka et al 2006, Skutlarek et al 2006, deVoogt et al 2006, Weremiuk et al 2006, Loos et al 2007, stormwater (Murakami et al 2009a, Xiao et al 2011, Nguyen et al 2011, groundwaters (Shultz et al 2004, Murakami et al 2009b and biota ranging from small invertebrates (vanLeeuwen et al 2006, Gulkowska et al 2006, Nakata et al 2006) to large mammals in a wide variety of habitats (Giesy and Kannan 2001). Few studies have examined a wide variety of sample types (municipal waters, natural waters and biota) collected within and near a single manufacturing plant.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Lake Maggiore in Italy gave similar very low levels of PFOS (3 ng l −1 ) and PFOA (9 ng l −1 ) in both lake and drinking water and the authors concluded that the treatment (slow sand filtration and chlorination) was ineffective in removing these chemicals (Loos et al 2007).…”
Section: Removal Of Perfluorooctane Sulphonate and Perfluorooctanoic mentioning
confidence: 97%
“…Drinking water concentrations were reported to be very similar, and the authors concluded that the removal systems of sand filtration and chlorination were inefficient at removing PFOS and PFOA. Lake Maggiore receives municipal, industrial and agricultural discharges (Loos et al 2007). Loos et al (2008) monitored selected stretches of the River Po and its major tributaries for PFCs.…”
Section: (C) Italymentioning
confidence: 99%
“…Wide dissemination at low concentrations mainly in the aquatic environment is evident today. Such concentrations have been detected in aquatic compartments such as influents [14][15][16] and effluents [17][18][19] from sewage treatment plants (STPs), surface waters (rivers, lakes, streams, estuaries, among others) [20][21][22][23][24], seawater [25], groundwater [26][27][28] and drinking water [29][30][31][32]. The scientific community is in broad agreement with the possibility that adverse effects may arise from the presence of pharmaceu-ticals not only for human health but also for aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%